Cultural China 2021 The Contemporary China Centre Review - Kehoe, Séagh; Wielander, Gerda (University of Westminster Press, 2022)
Cultural China is a unique annual publication for up-to-date, informed and accessible commentary about Chinese and Sinophone languages, cultural practices, politics and production, and their critical analysis. It builds on the University of Westminster's Contemporary China Centre Blog, providing additional reflective introductory pieces to contextualise each of the seven chapters. The articles in this Review speak to the challenging and eventful year that was 2021 as it unfolded across cultural China. Thematically, they range from health and medicine, environment, food, children and parenting, via film, red culture and calls for action. Many of the articles in this book focus on the People's Republic of China, but they also draw attention to the multiple Chinese and Sinophone cultural practices that exist within, across, and beyond national borders. The Review is distinctive in its cultural studies-based approach and contributes a much-needed critical perspective from the Humanities to the study of cultural China. It aims to promote interdisciplinary dialogue and debate about the social, cultural, political, and historical dynamics that inform life in cultural China today, offering academics, activists, practitioners, and politicians a key reference with which to situate current events in and relating to cultural China in a wider context.